2008
DOI: 10.1111/j.1944-9720.2008.tb03305.x
|View full text |Cite
|
Sign up to set email alerts
|

Student Voices: The Missing Link in the Spanish Heritage Language Debate

Abstract: Though much of the research looking at the issue of language in the Spanish heritage language field is intended to guide the Spanish heritage language teacher in the classroom, students' voices are often stifled. This article fills this gap by giving voice to students' opinions on language use in the Spanish heritage language classroom. Survey results from 152 Spanish heritage language students enrolled in an extensive Spanish heritage language program show that these students prefer to learn specific varietie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 18 publications
1
20
0
1
Order By: Relevance
“…Students would prefer to have both their oral and written language errors corrected, whereas teachers are more hesitant about error correction, especially in speaking. This result is consistent with Ducar's (2008) findings in which as much as 96% of students surveyed indicated that they wanted to be corrected. Students have a clear desire to receive feedback on their language production, perhaps because of their lack of confidence in their Spanish ability or simply because they have benefited from error correction in prior courses.…”
Section: Discussionsupporting
confidence: 91%
“…Students would prefer to have both their oral and written language errors corrected, whereas teachers are more hesitant about error correction, especially in speaking. This result is consistent with Ducar's (2008) findings in which as much as 96% of students surveyed indicated that they wanted to be corrected. Students have a clear desire to receive feedback on their language production, perhaps because of their lack of confidence in their Spanish ability or simply because they have benefited from error correction in prior courses.…”
Section: Discussionsupporting
confidence: 91%
“…A number of recent studies have investigated Spanish HL speakers at the university level, including learners at all proficiency levels (e.g., Beaudrie & Ducar, 2005;Blake & Zyzik, 2003;Edstrom, 2007;Lynch, 2008;Schwarzer & Petró n, 2005). These studies have offered insights about various aspects of HL learning and teaching, including reading abilities (e.g., Hislope, 2003); oral production (e.g., Achugar, 2003;Fairclough & Mrak, 2003); selfperceptions of Spanish skills (e.g., Hasson, 2008); sociocultural background variables that predict successful mastery of the HL (e.g., Oh & Au, 2005); HL and second language (L2) learners' interactions (e.g., Blake & Zyzik, 2003); written production and students' writing strategies (e.g., Martinez, 2007;Schwartz, 2003); similarities and differences between HL and L2 learners (e.g., Lynch, 2008;Montrul, 2005); students' opinions on language use in HL classes (Ducar, 2008); and HL speakers' perspectives in linguistically mixed classes, which include both L2 learners and native speakers of Spanish (Edstrom, 2007). Nonetheless, according to Schwarzer and Petró n (2005), ''Nowhere is the lack of information concerning heritage speakers more apparent than in the area of student attitude and perceptions'' (p. 569).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…An important action taken toward the remedy of this situation has been the development of courses and programs specifically designed for Spanish HSs. From the early claims made by Guadalupe Valdés and colleagues in the 1970s and 1980s advocating for SHL-specific pedagogies, the articulation of these educational alternatives has been characterized by an array of resources and perspectives, most notably the following: (1) the application of sociolinguistically informed curricula (e.g., Beaudrie, Ducar, & Potowski, 2014;Potowski & Lynch, 2014;Shin & Hudgens Henderson, 2017), (2) the implementation of principles of critical pedagogy and social justice (e.g., Abbott, 2018;Correa, 2011;Leeman, 2005;Leeman & Serafini, 2016), (3) the adoption of flexible approaches to language use (e.g., García, 2009;Shohamy, 2011;Prada & Nikula, to appear), (4) the inclusion of service learning or other forms of community engagement (e.g., Lowther Pereira, 2016; Pascual y Cabo, Prada, & Lowther Pereira, 2017), and (5) the attention and centralization of socioaffective factors, such as the notion of identity formation in the design and implementation of HL courses/programs (e.g., Hornberger & Wang, 2008;Ducar, 2008;Leeman, 2015;Parra, 2016;Potowski, 2012;Sánchez-Muñoz, 2016;Carreira & Beeman, 2014;Wilson & Martínez, 2011;Wilson & Ibarra, 2015). 3 The increasing trends in the implementation of such programs and courses in K-12 and postsecondary contexts across the country reflect the dynamics within the Hispanic community itself, which shows promising advances in areas such as education, employment, and linguistic vitality of Spanish (Krogstad, 2016).…”
Section: Spanish In the Context Of The United Statesmentioning
confidence: 99%